MIGRATION OF HEALTH PERSONNEL AND ITS IMPACT ON HEALTH SYSTEMS IN DEVELOPING COUNTRIES - Khan, Jahangir A (Journal of Ayub Medical College Abbottabad, 2007)
Human movement from one area to another area is a natural phenomena and this movement is predominantly due to economic and social reasons. Approximately 175 million people or 2.9% of the worlds' population currently live temporarily or permanently outside their countries of origin. The number of migrants has more than doubled since 1975. Sixty per cent of the world's migrants currently reside in the more developed regions and 40 per cent in the less developed regions. Most of the world's migrants live in Europe (56 million), Asia (50 million) and Northern America (41 million). Almost one of every 10 persons living in the more developed regions is a migrant. In contrast, nearly one of every 70 persons in developing countries is a migrant